A molecular dynamics study of adhesion of polyvinyl-chloride coatings to the aluminum surface. Issue 1 (1st July 2022) - Sharma, Amit; Sharma, Sumit
Abstract: Metal polymer interaction are difficult to measure experimentally, hence MD simulations are helpful in such problems to provide the vital information. Polyvinyl chloride is widely used in engineering applications due to its chemical and thermal stability and its barrier properties due to the C-Cl polar bond. Aluminum is also widely used in engineering structures as well as food and pharmaceutical packaging. Hence interaction or bonding between PVC and Al2 O3 is studied using MD simulations and interaction energy is calculated at different temperature to check the influence of temperature on adhesion between the two. The higher the absolute magnitude of interaction energy, the stronger the adhesion or bonding between metal and polymer. It was revealed that for the case of PVC coating on Al2 O3 the adhesion energy increases as temperature rises.